Cell mediated immunity to corn starch in starch-induced granulomatous peritonitis. Issue 3 (March 1976) - Goodacre, R L; Clancy, R L; Davidson, R A; Mullens, J E
Abstract : Two patients with histologically diagnosed starch induced granulomatous peritonitis (SGP) have been shown to have cell mediated immunity to corn starch using the techniques of macrophage migration inhibition and lymphocyte DNA synthesis. Control groups of normal subjects, patients with uncomplicated laparotomy, and patients with Crohn's disease were negative in both tests. Lymphocytes from two patients with band adhesions, one of whom had biopsy evidence of a granulomatous reaction to starch, were sensitized to starch. Cell mediated immunity to starch may contribute to the pathogenesis of SGP, and some band adhesions may be a chronic low grade manifestation of this disorder.